The Efficacy of Constitutions Birthed in the Midst of Post Armed Conflict Peace Processes: A Case Study of the South Sudan Permanent Constitution Making Process - Lui David Duku (Uganda Christian University, 2024)
The purpose of the study was to conduct a critical analysis of the South Sudan Permanent Constitution Making Process which commenced after the signing of the 2018 peace agreement. The study aimed at assessing whether the South Sudan Permanent Constitution Making Process conforms with the required standards of Constitution Making. The findings of the study were that the South Sudan Permanent Constitution Making Process has so many factors influencing it that could limit it from meeting the required standards of constitution making These factors include political influence to override the will of the people at the privilege of political interests, the time factor occasioned by a delay in implementing key tasks in the South Sudan Permanent Constitution Making Process among others. The study therefore concludes that the South Sudan Permanent Constitution Making Process should be subjected to a constitutional referendum both during the settlement of the contentious provisions at the making process and at the adoption stage. The study also recommends for a clear, transparent and proper procedure of selecting delegates to the National Constitutional Conference. This will protect the will of the people thus conforming with the ideal standard of constitution making.